PENGUASAAN TEKNOLOGI INFORMASI PENYULUH DALAM KEGIATAN PENYULUHAN PERTANIAN DI KABUPATEN KONAWE - Darsilan Dima; Salahuddin; Edi Syah Mihrad; Nurhayu Malik (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to analyze the mastery of information technology among extension workers in agricultural extension in Konawe Regency. The research was conducted in Konawe Regency, Southeast Sulawesi Province. The location of this research was determined purposively or intentionally. The respondents of this study were the entire population of this study, namely all food crop agricultural extension workers who were State Civil Apparatus (ASN) in Konawe Regency, amounting to 113 individuals (a saturated sample/census). The research variable is the mastery of information technology in agricultural extension, including the mastery of hardware (hardware) and the mastery of software (software) information technology for agricultural extension workers. The data analysis aimed to describe the state of the variable, namely the mastery of information technology by agricultural extension workers in Konawe Regency. Descriptive statistics with interval formula were employed to achieve this. The results indicated that the mastery of information technology by agricultural extension workers in Konawe Regency was in the medium category. Agricultural extension workers in Konawe Regency demonstrated the ability to master good information technology in carrying out their duties in agricultural extension. However, there is a need for improvement.